ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIK DAN SELF CONCEPT SISWA MTs PADA MATERI HIMPUNAN - Nurul Siti Aisyah; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to determine the ability of creative thinking of mathematics students at MTs Al-Basyariyah with indicator of the ability to think creatively mathematics students used was the fleuncy, flexibility originality and elaboration and to investigate the self concept of students at each point statement. This study was conducted to 36 students in MTs Al-Basyariyah using qualitative descriptive method. Instruments used in the form of four items of mathematical creative thinking abilities of students in the set and the questionnaire included 30 statements consisting of 23 statements positive and 7 negative statement. The conclusion of this study is the ability to think creatively mathematics students of MTs Al-Basyariyah still low with a percentage of 51% and self-concept is still low with a percentage of 43%.